Green Environment Modern Café Interior Design Using 3D Rendering Technique - Nicholas Tandria; Edi Wijaya; Feriani Astuti Tarigan (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The design of modern café interiors today not only emphasizes aesthetics but also considers environmental sustainability. This study aims to develop a café interior design using a green environment approach, which prioritizes energy efficiency, natural elements, and a comfortable atmosphere. The design process involved several stages, including observation, floor plan development, 3D modeling using SketchUp, and visual rendering with Lumion 6.0. A storyboard was created to guide camera movement during visualization, allowing each area to be presented systematically. The final result is an animation video that realistically showcases the interior, from the entrance to the outdoor area. Rendering was done offline to produce high-quality visuals, including natural lighting, realistic textures, and soft shadows. The final video was edited using Adobe Premiere Pro to add narration and background music. The findings indicate that 3D rendering technology is highly effective in conveying both aesthetic and environmentally friendly design concepts. This approach is expected to serve as a reference for developing sustainable interior designs, especially in public spaces such as cafés.